SOCIO-ECONOMIC DEVELOPMENT IN THE DANUBE DELTA BIOSPHERE RESERVE - NICOLETA DAMIAN (Revue Roumaine de Géographie)
Romania plays an important part in the EU Danube Region Strategy as co-ordinator country together with Austria. Its main goal is the socio-economic development of the Danube Region with strict observance of environmental protection principles. It is a priority task of this country as most of the Danube Delta Biosphere Reserve lies on its territory, a unique ecosystem in Europe and one of the largest natural wet zones in the world that has a threefold protection statute: UNESCO World Natural and Cultural Heritage Site, Wet Zone of International Importance (Ramsar Convention) and Biosphere Reserve of the “Man and Biosphere” UNESCO Programme. The Danube Delta Project aims at striking a balance between protecting this unique natural and cultural heritage and meeting the aspirations of the local population for better living conditions by creating the best opportunities for its economic development.